MENILIK KINERJA PRIVATISASI: Perbandingan Malaysia dan Indonesia - ropi, As (Pusjar SKPP Lembaga Administrasi Negara, 2008)
Indonesia and Malaysia are neighbor countries that have a lot of similarities in social and historical background. The governments of these two countries have implemented privatization policy in order to improve their economic performance. However, the policy gives the different impacts on both countries. The performance of privatization in Malaysia is very much better than it is in Indonesia. Therefore, Malaysia provides a lot of lessons that can be learned or followed by Indonesia. Indonesian Government must give more attention in these three aspects: the government’s commitment to the privatization policy, the integration between non-divestiture and divestiture strategies, and the obligation to change it’s paradigm that privatization is not merely an act of selling assets. Keywords: Indonesia, Malaysia, Privatization Policy, performance, selling assets.